La practica de las actividades fisicas indicen en la calidad de vida y salud de los habitantes de la parroquia Santiago. Loja 2014 - Quezada Castillo, Ernesto Vladimir (2016)
The title of this research is; THE PRACTICE OF PHYSICAL ACTIVITY AFFECTING THE QUALITY OF LIFE AND HEALTH OF RESIDENTS OF SANTIAGO PARISH. LOJA 2014. The central problem is; Lack of physical activity does not improve the quality of life and health of the inhabitants of the Santiago parish belonging to the canton Loja. The overall objective manifest; check if the lack of physical activity does not improve quality of life and health of the inhabitants of the parish Santiago. The methodology used was based on a study of transversal, descriptive and comparative type, the methods used were: method of direct observation, scientific method, descriptive, deductive and inductive statistical method, the pre experimental design was used as it was applied a pre-test and post-test, which yielded information gaps and then how to solve them with the alternative proposal. The instruments used were: observation, survey, test and plan activities. The study population is 40 persons belonging to the parish Santiago, they worked two variables: Physical Activity and Quality of Life and Health. Plan physical activities aimed at improving the quality of life and health was developed. According to the initial diagnosis we could realize that there was a high rate of physical inactivity, as the activities carried out were limited to daily as a result of this had diseases such as arthritis, diabetes and obesity, in addition to that was practicing bad habits such as alcoholism and smoking. Finally it was concluded that the selflessness and little importance is given to the massification of physical activity by the competent authorities, it is affecting the quality of life and health of the inhabitants of the parish Santiago. Therefore it was recommended to launch the resources and mechanisms necessary for the implementation of projects aimed at the massification of physical activity as a means to improve the quality of life and health.